2013
DOI: 10.1371/journal.pone.0084648
|View full text |Cite
|
Sign up to set email alerts
|

C6-Ceramide Nanoliposomes Target the Warburg Effect in Chronic Lymphocytic Leukemia

Abstract: Ceramide is a sphingolipid metabolite that induces cancer cell death. When C6-ceramide is encapsulated in a nanoliposome bilayer formulation, cell death is selectively induced in tumor models. However, the mechanism underlying this selectivity is unknown. As most tumors exhibit a preferential switch to glycolysis, as described in the “Warburg effect”, we hypothesize that ceramide nanoliposomes selectively target this glycolytic pathway in cancer. We utilize chronic lymphocytic leukemia (CLL) as a cancer model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 47 publications
3
49
1
Order By: Relevance
“…Of note, alterations in sphingolipid metabolism may play a crucial role in the regulation of cancer glycolytic capacity (48). In particular, C6-ceramide nanoliposomes have been shown to inhibit the glycolytic pathway in chronic lymphocytic leukemia (49), findings in line with results herein in AML. Our work shows that C6-ceramide-tamoxifen composite nanoliposomes were dosewise equal to or more effective in inducing apoptosis, suppressing glycolytic capacity, and inhibiting mitochondrial complex I respiration, compared with the combination regimens, demonstrating the utility of combinatorial Effect of composite nanoliposomes on apoptosis.…”
Section: Cellular Metabolism Of C6-ceramide and The Impact Of Tamoxifensupporting
confidence: 76%
“…Of note, alterations in sphingolipid metabolism may play a crucial role in the regulation of cancer glycolytic capacity (48). In particular, C6-ceramide nanoliposomes have been shown to inhibit the glycolytic pathway in chronic lymphocytic leukemia (49), findings in line with results herein in AML. Our work shows that C6-ceramide-tamoxifen composite nanoliposomes were dosewise equal to or more effective in inducing apoptosis, suppressing glycolytic capacity, and inhibiting mitochondrial complex I respiration, compared with the combination regimens, demonstrating the utility of combinatorial Effect of composite nanoliposomes on apoptosis.…”
Section: Cellular Metabolism Of C6-ceramide and The Impact Of Tamoxifensupporting
confidence: 76%
“…On the other hand, ceramide can inhibit PI3K/Akt cell signaling and when delivered in nanoliposomes, counteract the Warburg effect in cancer (Y. Jiang et al, 2011; Ryland et al, 2013; Tagaram et al, 2011). It is reasonable to speculate that different populations of exosomes – for example, depending on their ceramide content - may reprogram metabolism of cancer cells in distinct ways.…”
Section: Exosomes In Cancer: Target Tissue Biohacking and Hijacking Omentioning
confidence: 99%
“…The CNL has also been shown to decrease the expression of prosurvival gene products, such as survivin in large granulocyte lymphocyte (LGL) Brought to you by | University of California -Santa Barbara Authenticated Download Date | 6/23/15 3:30 PM leukemia (Liu et al, 2010b). Of critical importance and distinction from most anticancer compounds, the ability of ceramide to induce selective apoptosis in cancer cells is attributed to the inhibition of glycolysis, as demonstrated by the decreased expression of GAPDH in vitro and in vivo as well as decreased lactate and ATP concentrations in response to CNL treatment (Ryland et al, 2013). In cancerous cells, which commonly rely on the glycolytic pathway, a phenomenon known as the Warburg Effect, this inhibition results in cell death.…”
Section: The Cnl -Mechanism Of Action and Efficacymentioning
confidence: 99%
“…These PEGylated liposomes have a mean hydrodynamic diameter of 85 nm and contain 30 mol% C 6 -ceramide within the lipid bilayer. Interestingly, multiple studies have demonstrated that although the CNL carries two ceramide lipids, C 6 -ceramide and a C 8 -ceramide-PEG conjugate, only the C 6 -ceramide is pharmacologically active (Stover et al, 2005;Tran et al, 2008;Liu et al, 2010b;Jiang et al, 2011;Adiseshaiah et al, 2013;Ryland et al, 2013). The CNL formulation, which allows the active C 6 -ceramide to be both protected and delivered in aqueous solutions, was optimized for its stability, size and efficacy (Stover and Kester, 2003).…”
Section: Chemistry Manufacturing and Controls (Cmc)mentioning
confidence: 99%